Primary and albedo protons detected by the Lunar Lander Neutron and Dosimetry experiment on the lunar farside - Xu, Zigong; Guo, Jingnan; Wimmer-Schweingruber, Robert F.; Dobynde, Mikhail I.; Kühl, Patrick; Khaksarighiri, Salman; Zhang, Shenyi (Frontiers in Astronomy and Space Sciences, 2022)
The Lunar Lander Neutron and Dosimetry (LND) Experiment aboard the Chang'E-4 Lander on the lunar far-side measures energetic charged and neutral particles and monitors the corresponding radiation levels. During solar quiet times, galactic cosmic rays (GCRs) are the dominating component of charged particles on the lunar surface. Moreover, the interaction of GCRs with the lunar regolith also results in upward-directed albedo protons which are measured by the LND. In this work, we used calibrated LND data to study the GCR primary and albedo protons. We calculate the averaged GCR proton spectrum in the range of 9-368 MeV and the averaged albedo proton flux between 64.7 and 75.6 MeV from June 2019 (the 7th lunar day after Chang'E-4's landing) to July 2020 (the 20th lunar day). We compare the primary proton measurements of LND with the Electron Proton Helium INstrument (EPHIN) on SOHO. The comparison shows a reasonable agreement of the GCR proton spectra among different instruments and illustrates the capability of LND. Likewise, the albedo proton measurements of LND are also comparable with measurements by the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) during solar minimum. Our measurements confirm predictions from the Radiation Environment and Dose at the Moon (REDMoon) model. Finally, we provide the ratio of albedo protons to primary protons for measurements in the energy range of 64.7-75.6 MeV which confirm simulations over a broader energy range.